2010
DOI: 10.1590/s0102-311x2010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and musculoskeletal pain among Brazilian pottery workers

Abstract: In the municipality of Pedreira in São Paulo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…However, the prevalence of pain including upper back pain or lumbar region pain in this population of plastics industries workers (35.7%) was higher than among dentists (21%). The finding of pain in the lumbar region (28.9%) was more similar to the finding of 33% among workers in the ceramics industry 13 . Among ceramics workers 13 , the prevalence of pain in distal upper extremities was 35%; in the neck, 9%; in the shoulder, 9%.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the prevalence of pain including upper back pain or lumbar region pain in this population of plastics industries workers (35.7%) was higher than among dentists (21%). The finding of pain in the lumbar region (28.9%) was more similar to the finding of 33% among workers in the ceramics industry 13 . Among ceramics workers 13 , the prevalence of pain in distal upper extremities was 35%; in the neck, 9%; in the shoulder, 9%.…”
Section: Discussionsupporting
confidence: 81%
“…Picoloto & Silveira 12 , studying the industrial population of metal workers, found an overall prevalence of pain of 75.2%. On the other hand, a study of workers in the ceramic industry 13 found a 38.5% prevalence of pain in the previous twelve months, using a population of 90 individuals. This prevalence was higher among women, (46%), than among men, (16%).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The physical discomfort, the excessive work journey, inadequate and poorly designed workstation from the ergonomics perspective, intense rhythms of work, invariance of tasks, repeatability of movements, physical exertion, poor posture for a long period of time, mechanical pressure on certain segments of the body, static muscular work, shock and vibration, are some of the collaborative factors for the onset of WMSDs in mining workers or in other productive sectors [10,[13][14][15][16], corroborating with the low quality of life of the disabled workers, loss of productivity, lost workdays, spending with health care and payments to social security [17].…”
Section: Conclusion: Informal Workers From the Seridó Region In The Smentioning
confidence: 99%
“…The considerations around this public health problem are due to the fact that these disorders are common in both developed and developing countries [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%